PENGARUH INFORMASI PERPAJAKAN B ERBASIS COMMUNITY CLUSTER TERHADAP TINGKAT KEPATUHAN PAJAK PADA KANTOR PELAYANAN PRATAMA KOTA MAKASSAR - Faidul Adziem; Saida Said (Jurnal Riset Perpajakan: Amnesty, 2019)
Research aims to know to know whether taxation information based on social community cluster in the form of tax expo, socialization, website, tax and brochures are influential to the compliance of the taxpayer body at the Office of Service Makassar primary tax in south. The object of this research is financial management's income, the instrument in this study is through kuesiner to the parties concerned. The research also collects the relevant documents and supports the discussion of the research. The testing techniques used are simple linear regression. The results of the research processing of double linear regeresi data, the results of the T test required to test the significance of the constants and independent variables. There is a significant influence between the tax expo variables, tax socialization, tax brochures, tax-exempt websites in the positive direction, which means that the higher taxation information based on social community in the form of Tax Expo, Cheframonantonio Pratama Makassar Selatan